The Factors Contributing To EFL Students’ Difficulties In Paragraph Writing Course - Alwafa Amrullah; Rahmadi Nirwanto; Hesty Widiastuty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Writing is significantly essential for English as a foreign language and English as a second language. Students’ language learning has constantly been regarded as essential ability contributing to English learning. The purpose of this study was analyze factors contributing to students’ difficulties in paragraph writing course based on the students’ perceptions. This study used a descriptive qualitative method. The instruments used were interview and documentation. This study, the participants’ answers were purposive sampling and analyzed descriptively. The participants were 60 students who were taking paragraph writing course in second semester academic year 2022/2023 in English Language Education Program at IAIN Palangka Raya. The data analysis procedure of the research analysis were data condensation, demonstration, and verifying conclusion. The overall result based on the questionnaire, students found difficulties to use grammar. Based on the findings, there were two factors that caused students’ difficulties in writing. The two factors were internal and external. Internal factors consisted of self-motivation, self-confidence, lack of knowledge and feeling of under pressure External factors consisted of the teacher’s teaching style, classroom atmosphere, materials, and writing aspects. This research hopefully can help lecture in developing appropriate teaching techniques in writing and minimize students' difficulties in paragraph writing course.